Diagnostic value of ischemia severity at myocardial perfusion imaging in elderly persons with suspected coronary disease. Issue 10 (October 2016) - Canepa, Marco; Bezante, Gianpaolo; Vianello, Pierfilippo; Ameri, Pietro; Milaneschi, Yuri; Aste, Milena; Cavalla, Francesca; Bauckneht, Matteo; Marini, Cecilia; Balbi, Manrico; Brunelli, Claudio; Sambuceti, Gianmario
Abstract : Aims: Myocardial perfusion and ischemia scores obtained from myocardial perfusion scintigraphy (MPS) have strong independent prognostic value in elderly individuals without known coronary artery disease (CAD). Herein we aimed to assess their independent diagnostic value and accuracy for CAD while considering different thresholds of myocardial ischemia. Methods: We estimated the summed rest score (SRS), summed stress score (SSS) and summed difference score (SDS) in 322 elderly individuals (mean age 72 ± 7 years, 68% men) who underwent coronary angiography following an MPS. Abnormal perfusion at stress was defined as an SSS greater than 3, and ischemia as an SDS of at least 2, and further categorized as mild (2–4), moderate (5–7) or severe (>7). Multivariate logistic regressions were used to establish the independent diagnostic value and accuracy of MPS parameters. Results: CAD was diagnosed in 182 individuals (56%). In multivariate analysis accounting for clinical variables associated with CAD including the Framingham risk score, both SRS [odds ratio (OR) 1.09, 95% confidence interval (CI) 1.01–1.18, P = 0.03] and SSS (OR 1.10, 95% CI 1.04–1.16, P = 0.0006) and SDS (OR 1.12, 95% CI 1.04–1.21, P = 0.003) were independently associated with CAD. An SSS greater than 3 was also independently associated with CAD (OR 2.51, 95% CI 1.43–4.39, P = 0.0013), whereas an SDS of 2 or greater was not (OR 1.62, 95% CI 0.89–2.93, P = 0.12), but only when at least 5 (OR 2.31, 95% CI 1.32–4.03, P = 0.003). The probability of CAD was proportional to the amount of myocardial ischemia in those with an SSS greater than 3, and lower and comparable in those with an SSS of at least 3 or an SSS greater than 3 with SDS of 1 or less ( P = 0.19). Increasing the threshold of myocardial ischemia determined a decrease in sensitivity and increase in specificity of MPS for both diagnosis and severity of CAD. Conclusion: We established the diagnostic value and accuracy of continuous scores and thresholds of abnormal myocardial perfusion and ischemia previously validated in prognostic studies. Their more widespread use could potentially improve the diagnostic yield of coronary angiography in elderly individuals with suspected CAD. Abstract : Supplemental Digital Content is available in the text